Calling the Police: Dispatchers as Important Interpreters and Manufacturers of Calls for Service Data. (9th March 2020) - Simpson, Rylan
Abstract: Policing has historically been conceptualized as a team sport which requires the work of many to produce the output of one. Although police officers have been the focus of much policing research, it is important to recognize that the work of officers hinges upon the work of dispatchers. As a lifeline for both citizens and police officers, dispatchers play an integral role in ensuring that help is provided where help is required via their management of the emergency (911) telephone and radio system. Despite their importance, however, dispatchers have largely been excluded from mainstream criminological scholarship. Supplemented by a narrative review of the scant literature on the subject of dispatching, this commentary illustrates the important role of dispatchers in policing operations, theorizes the dearth of research regarding dispatchers, and calls for future research to better understand their discretionary and interpretive work. This commentary thus casts light on these highly important but understudied and undertheorized figures in the policing nexus.